Measurement of the branching fractions of the radiative charm decays D0→K̄*0γ and D0→ γ - Aubert, B; Bona, M; Karyotakis, Y; Lees, J; Poireau, V; Prencipe, E; Prudent, X; Tisserand, V; Tico, J; Grauges, E; Lopez, L; Palano, A; et al. (2008)
We present a measurement of the branching fractions for the Cabibbo-favored radiative decay D0→K̄*0γ and the Cabibbo-suppressed radiative decay D0→ γ. These measurements are based on a data sample corresponding to an integrated luminosity of 387.1fb-1 and recorded with the BABAR detector at the PEP-II e+e- asymmetric-energy collider operating at center-of-mass energies 10.58 and 10.54 GeV. We measure the branching fractions relative to the well-studied decay D0→K-π+ and find B(D0→K̄ *0γ)/B(D0→K-π+)=(8.43±0.51±0.70)×10-3 and B(D0→ γ)/B(D0→K-π+)=(7.15±0.78±0.69)×10- 4, where the first error is statistical and the second is systematic. This is the first observation of the decay mode D0→K̄*0γ. © 2008 The American Physical Society.